PENDIDIKAN KARAKTER MELALUI KITAB TA’LIM AL-MUTA’ALLIM DI PESANTREN ABU BAKAR AS-SIDDIQ BULUKUMBA - Nurwahida; Abdurrahman; Samsuddin; Iskandar (IMTIYAZ: Jurnal Ilmu Keislaman, 2025)
This study aims to examine the implementation of character education based on the Ta’limul Muta’allim book in shaping the akhlaqul karimah (noble character) of students at Pesantren Abu Bakar Ash-Shiddiq Wahdah Islamiyah Bulukumba. Using a qualitative method, data were collected through interviews, observations, and documentation. The findings indicate that key values such as honesty, discipline, patience, and respect for teachers are effectively instilled through structured learning of Ta’limul Muta’allim. The teaching process involves traditional methods such as lectures and discussions, combined with role modeling and direct daily practice. These approaches have shown a positive impact on students’ behavior, enhancing their awareness and application of Islamic ethics in both academic and social contexts. However, the study also highlights challenges such as the declining interest in classical Islamic texts and the growing influence of modern culture among youth. Overall, the research concludes that Ta’limul Muta’allim remains a relevant and effective tool for character education in pesantren, especially when supported by contextual and innovative teaching strategies adapted to contemporary challenges.